Impact of Endovascular Revascularization on Functional Connectivity and Cognition in Symptomatic Chronic Internal Carotid Artery Occlusion Patients: A Preliminary Exploratory Study - Renjie Ji; Shixin Zhang; Hanfeng Chen; Chunlan Deng; Ziqi Xu; Jie Zhang; Benyan Luo (Journal of Integrative Neuroscience)
Background: Symptomatic chronic internal carotid artery occlusion (CICAO) may lead to stroke and cognitive decline. Although endovascular recanalization has been proven to reduce the risk of future strokes, the effect on cognition remains controversial and requires further exploration. We explored alterations in functional connectivity (FC) and their associations with cognition in patients with symptomatic CICAO before and after carotid revascularization. Methods: Eighteen patients with unilateral CICAO and fifteen healthy controls (HCs) were enrolled. Resting-state functional magnetic resonance imaging (rs-fMRI) and neuropsychological assessment were performed on all participants, before and after 6 months post-recanalization in the patient group. FC alterations in multiple brain networks and their correlations with cognitive scores were analyzed. Results: The FC of the CICAO group were markedly lower relative to the HC group for the following: the dorsal attention network (DAN) with the ipsilateral (occlusion side, right) middle frontal gyrus and frontal pole; the default mode network (DMN) with the ipsilateral angular gyrus; the visual network (VN) with the ipsilateral fusiform gyrus; and the frontoparietal network (FPN) with middle temporal gyrus on the side contralateral to the occlusion. The decreased FC of the DAN exhibited a positive association with the total score of the Mini-Mental State Examination (MMSE, r = 0.499, p = 0.049), Montreal Cognitive Assessment (MoCA, r = 0.515, p = 0.041), and Backward Digit Span Test (BDST, r = 0.594, p = 0.015), and negatively correlated with the score of Trail Making Test (TMT)-A (r = –0.563, p = 0.023) and TMT-B (r = –0.602, p = 0.014). The CICAO group exhibited significantly increased FC of the DMN seed region with the middle occipital gyrus ipsilateral to the occlusion. Additionally, the VN seed region demonstrated increased FC with the fusiform gyrus ipsilateral to the occlusion following endovascular recanalization. The preoperative FC values of the DMN exhibited a strong positive association with the improvement in TMT-A score (r = 0.629, p = 0.021). Conclusion: Our exploratory study found that FC disruption may induce cognitive decline in symptomatic CICAO patients. Endovascular recanalization may improve FC within key brain networks, supporting cognitive improvement. The baseline DMN FC was significantly associated with the postoperative improvement in TMT-A scores, suggesting that preoperative DMN FC could serve as a potential predictor of cognitive recovery. Clinical Trial registration: NCT05292729. Registered 1 December 2021, https://clinicaltrials.gov/study/NCT05292729?intr=NCT05292729&rank=1.